Cultivating Qur’anic Character Through Gratitude-Based Learning: A Qualitative Action Research at TPA Muhajirin, Alafan, Simeulue - Zikra, Vini Nur (The Indonesian Institute of Science and Technology Research, 2025)
This study explores a gratitude-centered Islamic learning model implemented in TPA Muhajirin, Alafan, Simeulue, through a qualitative action research design. The program, held every Monday, Wednesday, and Friday afternoon, focuses on muraja’ah, makhārijul huruf practice, and basic Islamic values. Despite limited facilities, learning is consistently filled with joy, enthusiasm, and deep spiritual meaning. The research draws upon reflective cycles of planning, acting, observing, and reflecting, supported by relevant literature on Islamic pedagogy, affective learning, and community-based education. Data were collected through observation, reflective journals, informal interviews, and documentation. Results show that gratitude-based learning strengthens students’ Qur’anic literacy, fosters moral awareness, and enhances classroom engagement. Three thematic findings are presented: emotional and spiritual engagement, improvement in Qur’anic reading fluency, and growth in Islamic character and social cooperation. The study offers practical insights for educators working in resource-limited settings, highlighting that sincere intention, consistency, and gratitude can sustain impactful religious education. Recommendations emphasize supporting community-based Islamic learning institutions and integrating affective components into Qur’anic pedagogy.